Anodic electro‐fermentation: Anaerobic production of L‐Lysine by recombinant Corynebacterium glutamicum. Issue 6 (24th March 2018) - Vassilev, Igor; Gießelmann, Gideon; Schwechheimer, Susanne K.; Wittmann, Christoph; Virdis, Bernardino; Krömer, Jens O.
Abstract: Microbial electrochemical technologies (MET) are promising to drive metabolic processes for the production of chemicals of interest. They provide microorganisms with an electrode as an electron sink or an electron source to stabilize their redox and/or energy state. Here, we applied an anode as additional electron sink to enhance the anoxic metabolism of the industrial bacterium Corynebacterium glutamicum through an anodic electro‐fermentation. In using ferricyanide as extracellular electron carrier, anaerobic growth was enabled and the feedback‐deregulated mutant Corynebacterium glutamicum lysC further accumulated L‐lysine. Under such oxidizing conditions we achieved L‐lysine titers of 2.9 mM at rates of 0.2 mmol/L/hr. That titer is comparable to recently reported L‐lysine concentrations achieved by anaerobic production under reductive conditions (cathodic electro‐fermentation). However unlike other studies, our oxidative conditions allowed anaerobic cell growth, indicating an improved cellular energy supply during anodic electro‐fermentation. In that light, we propose anodic electro‐fermentation as the right choice to support C. glutamicum stabilizing its redox and energy state and empower a stable anaerobic production of L‐lysine. Abstract : Growth and aerobic production of amino acids and various chemicals by important industrial bacterium, Corynebacterium glutamicum relies on oxygen as terminal electron acceptor, which limits product yields through substrate loss. To overcome the oxygen dependency, the authors provide the bacterium an alternative terminal electron acceptor, ferricyanide, which can be continuously re‐oxidized by an anode in a bioelectrochemical system. In that way, anodic electro‐fermentation enabled anaerobic growth, glucose consumption and production of organic acids and L‐lysine.